PENGGUNAAN MEDIA KANTONG PAPAN BANGUN DATAR UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI BVANGUN DATAR SISWA KELAS II SDN KALISALAM 2 KABUPATEN PROBOLINGGO - Isma Aini Nafis; Didit Yulian Kasdriyanto; Faridahtul Jannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research was conducted based on the background of low learning outcomes in mathematics subjects at SDN Kalisalam 2 Probolinggo district where the intended students are grade II students, students activeness in learning that is lacking and not based on media, model, or methods of learning. For this reason, researchers conducted research aimed at activating student learning and improving student learning outcomes in the learning improvements carried out. This research uses the Classroom Action Research Method. This research has 2 cycles, of which each cycle has 2 meetings. Classroom action research has 4 stages, namely planning, activities, and reflection. Classroom Action Research method by collecting data through instruments in the form of tests to conduct assessments and test the achievement of competencies. So the use of Classroom Action Research methods will provide effective results. This research was conducted on February 08, 2025 to February 24, 2025 in two cycles, namely cycle I and cycle II. In cycle I there were 6 students out of 13 students who achieved learning completeness (46.15%), while in cycle II, the number of students who achieved learning completeness increased to 10 students out of 13 students (76.92%). With the increase in learning outcomes this occurred due to the application of media that was not only pictures, but included games that were able to make students excited about learning. The method used is the lecture method by using the Flat Building Board Bag (PABATAR) media. It can be concluded that the Flat Building Board Bag (PABATAR) media can improve the learning outcomes of grade II students of SDN Kalisalam 2 Probolinggo Regency.